2023
DOI: 10.1161/jaha.122.027581
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Role of Invasive Left Heart Catheterization in Patients Suspected of Heart Failure With Preserved Ejection Fraction

Abstract: Background Recently, diastolic stress testing and invasive hemodynamic measurements have been emphasized for diagnosis of heart failure with preserved ejection fraction (HFpEF) because when determined using noninvasive parameters it can fall into a nondiagnostic intermediate range. The current study evaluated the discriminative and prognostic roles of invasive measured left ventricular end‐diastolic pressure in the population with suspected HFpEF, particularly for patients with intermediate Heart F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, evaluating this HFA-PEFF is a widely used scoring system for diagnosing HFpEF. However, evaluating this scoring system requires numerous parameters, including echocardiography, NT-proBNP, and atrial fibrillation diagnosis [17,25]. Through our study, LA strain indices have demonstrated an AUC equivalent to that of the HFA-PEFF score.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, evaluating this HFA-PEFF is a widely used scoring system for diagnosing HFpEF. However, evaluating this scoring system requires numerous parameters, including echocardiography, NT-proBNP, and atrial fibrillation diagnosis [17,25]. Through our study, LA strain indices have demonstrated an AUC equivalent to that of the HFA-PEFF score.…”
Section: Discussionmentioning
confidence: 67%
“…However, evaluating this scoring system requires numerous parameters, including echocardiography, NT-proBNP, and atrial fibrillation diagnosis [17,25]. Through In conclusion, LA parameters on speckle tracking echocardiography may be useful in diagnosing HFpEF and integration into the 2016 EACVI/ASE criteria will improve diagnostic effectiveness with accuracy not inferior to conventional echocardiographic parameters for diagnosing HFpEF.…”
Section: Discussionmentioning
confidence: 98%
“…In this issue of the Journal of the American Heart Association ( JAHA ), Ki Hong Choi et al publish an important study in a Korean population to show the diagnostic and prognostic value of left ventricular end‐diastolic pressure (LVEDP) in patients with suspected heart failure with preserved ejection fraction (HFpEF). 1 Of 404 patients with suspected HFpEF, LVEDP was ≥16 mm Hg in 80%, consistent with HFpEF, and this group of patients was found to have higher heart failure assoication‐pretest assessment, echocardiography, functional testing, and final etiology (HFA‐PEFF) scores than the 20% of patients with noncardiac dyspnea who had LVEDP <16 mm Hg. Although the HFA‐PEFF score was associated with a significantly higher 10‐year risk of death‐ or heart failure‐related events, the score was in the intermediate range for a significant proportion (56%) of the study patients.…”
mentioning
confidence: 82%
“…34 A portion of studies examined the value of the H 2 FPEF and HFA-PEFF scores for predicting unfavourable outcomes in HFpEF patients, and the conclusions are not consistent. Most studies have shown that both tools can be used to assessing HFpEF prognosis, 35,36 and higher scores are associated with more all-cause mortality and rehospitalisation, [37][38][39][40] including in patients with cardiac valve surgery or cardiac amyloidosis. [41][42][43] Compared to HFA-PEFF algorithm, H 2 FPEF score can also be useful to predetermine cardiovascular and HF-related events.…”
Section: Prognosis Of Hfpefmentioning
confidence: 99%